Dignidade da pessoa humana e acesso à justiça : meios alternativos para desjudicialização em matéria penal - Cavalcante, Vinícius Rodrigues (2017)
The objective of this study is to analyze the current scenario of the Brazilian Criminal Justice, crowded with processes of the most varied species, which generates a great dissatisfaction in the population, due to the delay in the jurisdictional rendering. Given this panorama of crisis of the Judiciary, an approach is taken on the principles of minimum intervention and insignificance, which are real tools to remove certain conduct from the criminal sphere through solutions from extrajudicial processes of social pacification. These instruments are an expression of the constitutional guarantee of access to justice in the light of the constitutional principle of the dignity of the human person. In order to obtain this answer, modern constitutional hermeneutics is used as a way to enable real access to justice through mechanisms for resolving conflicts that are far from the Judiciary, such as conciliation, mediation, arbitration and, in the sphere of criminal law, The Restorative Justice. Disjudicialization goes against the culture of litigation and the universalization of judicial protection disseminated in Brazilian society, but it finds shelter in the avant-garde constitutional hermeneutics. It is proposed to change culture in legal education in order to discourage the culture of litigation in order to assess the culture of peace and the implementation of alternative means of conflict resolution.